State of index-based crop insurance services in East Africa: Findings from a scoping study to establish the state of index-based crop insurance services in Kenya, Tanzania and Uganda - Osumba, Joab J.L.; Recha, John W.M.; Demissie, Teferi Dejene; Shilomboleni, Helena; Radeny, Maren A.O.; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Index-based insurance is increasingly recognized as an important risk management tool against the impacts of climate change and variability. Index-based insurance differs from traditional insurance because compensation is done based on the losses of a specific client. The insurance avoids costs related to assessing and validating policyholder losses and minimizes moral hazard and adverse selection problems, given that policyholders cannot affect the distribution of payouts ex ante and the historical distribution of the index is observable to both the insurer and the policyholder (Miranda and Farrin 2012). For these reasons, index-based insurance offers a potentially cost-effective means of managing smallholder production risks and has the potential to strengthen resilience by cushioning the risk of losses and debt. However, the uptake of index-based insurance is still low among farmers in developing countries. Is this the case in East Africa? This study sought to answer the question by assessing the state of index-based crop insurance services in Kenya, Tanzania and Uganda. The study was conducted as a requirement for the Climate Resilient Agribusiness for Tomorrow (CRAFT) project, under strategic objective four which aims at increasing incomes for smallholder farmers and small and medium enterprises (SMEs) through increased adoption of climate-smart practices and technologies.